2007
DOI: 10.1007/s00441-006-0374-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of adenosine receptors in rat cochlea

Abstract: Adenosine is a constitutive cell metabolite that can be released from cells via specific bi-directional transporters and is an end-point for nucleotide hydrolysis. In the extracellular space, adenosine becomes a signalling molecule for P1 (adenosine) receptors that modulate physiological responses in a wide range of mammalian tissues. Whereas adenosine signalling has been implicated in the regulation of cochlear blood flow and in cochlear protection from oxidative damage, the potential roles for adenosine sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…Further, the expression level of A 1 and A 3 receptors was found to be higher in the well-vascularized cochlear lateral wall and organ of Corti than in the eighth nerve of chinchilla cochlea (Ford et al, 1997). Recently, mRNA transcripts for all four subtypes of adenosine receptors were detected in rat cochlear tissue, and adenosine receptors were found to be differentially expressed in the sensory hair cells and supporting cells of the organ of Corti, spiral ganglion neurons, and cochlear vasculature (Vlajkovic et al, 2007) Several studies have indicated the presence in cochlear tissues of adenosine receptors that are thought to be activated through generation of reactive oxygen species (ROS) in response to various stresses to the inner ear. Noise exposure induced A 1 receptor expression, which might be mediated, in part, through generation of ROS and activation of nuclear factor (NF)-kB (Ramkumar et al, 2004).…”
Section: P1 (A) Adenosine Receptorsmentioning
confidence: 99%
“…Further, the expression level of A 1 and A 3 receptors was found to be higher in the well-vascularized cochlear lateral wall and organ of Corti than in the eighth nerve of chinchilla cochlea (Ford et al, 1997). Recently, mRNA transcripts for all four subtypes of adenosine receptors were detected in rat cochlear tissue, and adenosine receptors were found to be differentially expressed in the sensory hair cells and supporting cells of the organ of Corti, spiral ganglion neurons, and cochlear vasculature (Vlajkovic et al, 2007) Several studies have indicated the presence in cochlear tissues of adenosine receptors that are thought to be activated through generation of reactive oxygen species (ROS) in response to various stresses to the inner ear. Noise exposure induced A 1 receptor expression, which might be mediated, in part, through generation of ROS and activation of nuclear factor (NF)-kB (Ramkumar et al, 2004).…”
Section: P1 (A) Adenosine Receptorsmentioning
confidence: 99%
“…An immunohistochemical study showed expression of three subtypes of P1 adenosine receptors (A 1 R, A 2A R, and A 3 R) in both IHCs and SGNs of adult rats [41], but develop- To date, there is little evidence of functional P1 receptors in the inner ear. In the cochlear partition, perfusion of adenosine in either perilymph or endolymph showed no changes in cochlear physiological parameters such as CAP [23,25] and no in vitro study has been published.…”
Section: P1 Receptors In the Inner Earmentioning
confidence: 99%
“…While there has been an extensive analysis of P2X receptor expression both in the developing and mature cochlea across several species (for reviews, see [1,22]), and adenosine receptor and ecto-nucleotidase activity has been established [23][24][25]. The sites and mechanisms of action of P2Y receptor activity in the cochlea are still emerging.…”
Section: Introductionmentioning
confidence: 99%